2018
DOI: 10.15673/fst.v12i1.842
|View full text |Cite
|
Sign up to set email alerts
|

Composting of Organic Waste With the Use of Mineral Additives

Abstract: Aerobic composting is one of the best available technologies for an integrated waste management system in terms of minimizing the anthropogenic impact on the environment, complying with the latest domestic and foreign developments, economic and practical acceptance of the technology. Organic production is rapidly spreading in the world as a holistic system of rational nature management that becomes the basis for the use of modern composting technologies for organic raw materials to obtain a quality product of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…There they have shown that with the existing methods of energy conversion the additional synthetic gas energy output obtained with plasma generators is not able to cover real costs of consumed electrical power. Vegetable and food wastes may be utilized by composting with special mineral additives [22], by means of decomposition in biogas equipment installations with subsequent thermal treatment of fermented residue in a pyrolysis furnace [23]. However, for unsorted solid municipal wastes such ways of utilization are technologically and economically inexpedi-ent.…”
Section: Introductionmentioning
confidence: 99%
“…There they have shown that with the existing methods of energy conversion the additional synthetic gas energy output obtained with plasma generators is not able to cover real costs of consumed electrical power. Vegetable and food wastes may be utilized by composting with special mineral additives [22], by means of decomposition in biogas equipment installations with subsequent thermal treatment of fermented residue in a pyrolysis furnace [23]. However, for unsorted solid municipal wastes such ways of utilization are technologically and economically inexpedi-ent.…”
Section: Introductionmentioning
confidence: 99%